The Role of Work Engagement in Moderating the Impact of Job Characteristics, Perceived Organizational Support, and Self-Efficacy on Job Satisfaction - Adhe Rachman Sulistyo; Suhartini Suhartini (Fakultas Ekonomi, Universitas Bangka Belitung, 2019)
This research is aimed at figuring out the extent to which job characteristics, perceived organizational support and self-efficacy affect job satisfaction with work engagement serving as an intervening variable. The respondents of this research were 101 employees of the Centre for the Development and Empowerment of Educators and Educational Personnel (P4TK) of Art and Culture of Yogyakarta. The data were collected using questionnaires. The data were analyzed quantitatively and qualitatively. The quantitative analysis techniques used in this research were t-test, F-test, multiple regression analysis and path analysis. The research yielded some results. Firstly, job characteristics and self-efficacy had a significant effect on work engagement and perceived organizational support did not have any significant effect on work engagement, but together it had a significant effect on work engagement. Secondly, job characteristics and perceived organizational support had a significant effect on job satisfaction, and self-efficacy did not have any significant effect on job satisfaction, but together it had a significant effect on job satisfaction. Thirdly, work engagement had a significant effect on job satisfaction. Fourthly, job characteristics and perceived organizational support had a greater effect on job satisfaction directly, and self-efficacy had a greater effect on job satisfaction indirectly through work engagement. The results of this research can be used as a reference for P4TK to improve employees' job satisfaction, and ultimately, support the achievement of organizational goals.